Revenge of the whale : the true story of the whaleship Essex - Philbrick, Nathaniel (G.P. Putnam, 2002)
Recounts the 1820 sinking of the whaleship "Essex" by an enraged sperm whale and how the crew of young men survived against impossible odds. Based on the author's adult book "In the Heart of the Sea."